Embodied Interaction and Spatial Presence in Virtual Immersive Media Systems - Qiu, Minjun (Transactions on Social Science, Education and Humanities Research, 2026)
This paper explores the connection between EI and SP in virtual immersive media systems, such as virtual reality (VR), augmented reality (AR), and 360-degree video platforms. The study used a post-positivist mixed-methods design, collecting condition level observations from 171 adult participants to investigate the relationship between system-level interaction variables (tracking fidelity, sensorimotor coupling quality and end-to-end latency) and their subjective experience of spatial presence as assessed on the Igroup Presence Questionnaire. The findings show that the presence dimensions are strongly affected (η²p = .58–.60) by the platform condition, and that VR (6-DOF) condition is generally superior to AR condition and 360-video condition. The strongest predictor of presence (r = −.81) and variance in general presence scores was system latency. The outcomes not only confirm the integrated five-layer interaction model but also directly impact the immersive content design, haptic feedback engineering, and user onboarding strategy.